2019
DOI: 10.1186/s12889-019-7930-7
|View full text |Cite
|
Sign up to set email alerts
|

Child diet and health outcomes of the simple suppers program: a 10-week, 2-group quasi-experimental family meals trial

Abstract: BackgroundRacial minority children, particularly from low-income households, are at risk for obesity. Family meals have a protective effect on child nutritional health. However, the current evidence is limited in racial and socioeconomic diversity. The objective of this study was to evaluate the impact of a family meals intervention, Simple Suppers, on improvements in diet and health outcomes from baseline (T0) to post-intervention (T1) in intervention compared to waitlist control participants, and determine r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 70 publications
0
16
0
Order By: Relevance
“…However, another family-based intervention, Healthy Habits, Healthy Homes, was effective at reducing child television viewing in general, though the intervention did not target reducing television viewing in the mealtime context specifically [ 31 ]. More recently, a family intervention program that focuses on teaching low-income racially diverse parents and children meal preparation skills, Simple Suppers, has been successful at reducing television viewing during mealtimes [ 32 ]. Still, more research is needed in this area, especially regarding culturally tailored programs for Hispanic families.…”
Section: Discussionmentioning
confidence: 99%
“…However, another family-based intervention, Healthy Habits, Healthy Homes, was effective at reducing child television viewing in general, though the intervention did not target reducing television viewing in the mealtime context specifically [ 31 ]. More recently, a family intervention program that focuses on teaching low-income racially diverse parents and children meal preparation skills, Simple Suppers, has been successful at reducing television viewing during mealtimes [ 32 ]. Still, more research is needed in this area, especially regarding culturally tailored programs for Hispanic families.…”
Section: Discussionmentioning
confidence: 99%
“…SSB consumption was not significantly changed after the program, even though the 43% reduction in its consumption should be highlighted. Another 10-week intervention in 4-10 years old children based on family meals did not find intervention effects on SSB consumption [39]. Likewise, Haerens et al [40] found no positive effects on the consumption of SSB in 11-15 years olds after a school-based program.…”
Section: Discussionmentioning
confidence: 92%
“…The presence of the fruits in children dietary became "weekly" instead of "daily" (Figure 6 and Figure 7). The finding should worry because the beneficial of fresh fruits and vegetables consumption was demonstrated, and highly recommended due to low caloric content, supply for micronutrients and fiber [14]. Fruits and vegetables are essential for prevention of the obesity.…”
Section: Resultsmentioning
confidence: 99%